Male Date Palm Chlorotype Selection Based on Fertility, Metaxenia, and Transcription Aspects - Hammadi Hamza; Mohamed Ali Benabderrahim; Achwak Boualleg; Federico Sebastiani; Faouzi Haouala; Mokhtar Rejili (Horticulturae, 2025)
This study evaluated the influence of different male date palm cultivars, distinguished by their chloroplast haplotypes, on pollen quality, pollination efficiency, metaxenia effects, and gene expression during fruit development. Chloroplast DNA analysis of 37 male trees revealed multiple haplotypes, from which cultivars B25, P8, C22, and B46 were selected for further investigation. Pollen viability varied significantly among cultivars, with P8 and B25 exhibiting the highest germination rates and pollen tube elongation, while C22 showed the lowest. These differences correlated with pollination success: P8 and B25 achieved fertilization rates near 99%, whereas C22 remained below 43%. Pollination outcomes also varied in fruit traits. Despite its low pollen performance, C22 induced the production of larger fruits at the Bleh (Kimri) stage, potentially due to compensatory physiological mechanisms. Phytochemical profiling revealed significant cultivar effects: fruits from B25-pollinated trees had with lower moisture and polyphenol content but the higher sugar levels and soluble solids, suggesting accelerated maturation. Ripening patterns confirmed this finding, with B25 promoting the earliest ripening and B46 causing the most delayed. Gene expression analysis supported these phenotypic differences. Fruits pollinated by P8, B25, and B46 exhibited elevated levels of cell-division-related transcripts, particularly the PdCD_1 gene (PDK_XM_008786146.4, a gene encoding a cell division control protein), which was most abundant in P8. In contrast, fruits from C22-pollinated trees had the lowest expression of growth-related genes, suggesting a shift toward cell expansion rather than division. Overall, the results show the critical role of male genotype in influencing fertilization outcomes and fruit development, offering valuable insights for targeted breeding strategies at enhancing date palm productivity and fruit quality.